ETHNOBOTANICAL STUDY OF PLANTS USED FOR HAIR CARE BY GAYO WOMENS IN BENER MERIAH - Ernilasari Ernilasari; Saudah Saudah; Rizky Ahadi; Rubiah Rubiah (Universitas Islam Negeri Ar-Raniry, 2023)
Gayo women in Bener Meriah Regency are one of the communities that still maintain the use of plants as cosmetics, one of which is used as hair care. Each ethnic group has its own way of using plants according to local wisdom, but it’s knowledge is only passed down orally from generation to generation without any written documentation. This research aims to find out about the species of plants used as hair care by Gayo women in Bener Meriah. This research uses an exploratory survey method. Sample determination was carried out using snaw ball sampling. The sample includes housewives and youth from the Gayo tribe, as well as people who use plants as hair care. The data was analyzed descriptively qualitatively and the data was displayed in the form of tables and figures. The results of the research show that there are 11 plant species used in Gayo women's hair care.